Understanding the impact of the economic crisis on child and maternal health among the poor: Opportunities for South Asia - Azra Abdul Cader; Lakwimashi Perera (Asian Development Bank Institute (ADBI), 2011)
The economic crisis hit many countries in 2007 and the effects are still being felt, especially in poorer developing nations. Much of the debate surrounding the economic crisis and its impacts has focused on the financial and economic aspects - import/export impacts, economic growth losses, labor force cutbacks, and fiscal imbalances. The social impact, especially on poor and vulnerable groups, has received less mention. Yet, if countries are to address the overall impacts of the economic crisis, it is vital that they also consider investing time and money to deal with social impacts more effectively. There are fears, however, that a reduction in spending on vital sectors (including the healthcare sector) to ensure economic recovery could affect poor and vulnerable populations and, in turn, erase the progress that has been made thus far. The decision to reduce such spending could also come from donors, who tend to favor a market-led recovery process in economic crises, thereby neglecting vital social service sectors that cater to the needs of poor populations. This spending can supplement government services or fill resource gaps and as a result reductions could have negative impacts on beneficiary populations, particularly the poor and vulnerable. Addressing child and maternal health issues within the context of the economic crisis is one key area to consider given its short, medium, and long-term effects on populations in developing countries. In South Asian countries, child and maternal health-related indicators tend to be disturbing despite the rapid growth rates in many of these countries. The number of infant deaths is still quite high, nutrition of children and women continues to be problematic, and maternal health and pre/post natal care remains poor. This paper presents an overview of child and maternal health in the South Asia region, but also recommends that interventions take into account a series of factors if the impacts of the economic crisis are to be minimized: There is a need for more information and research on the impacts of the crisis; Investing in social protection and safety nets is imperative; Food security should be integrated into social protection; Vulnerable households require support to cope with the crisis despite their own efforts and coping strategies; State investments that support vulnerable populations should be protected in times of crisis.
Keywords: I10; Y20; 330; Wirtschaftskrise; Gesundheit; Armut; Kinder; Erwachsene; Nahrungsmittelversorgung; Soziale Sicherung; Südasien